Development of Interactive Learning Media Flip-Book Using Kvisoft Flipbook Maker Based on Local Culture Arts - Reni Ariska Putri; Sri Uchtiawati; Nur Fauziyah; Syaiful Huda (Universitas Muhammadiyah Gresik, 2020)
Development of interactive learning media flip book using Kvisoft flipbook maker based on local culture and art is one way to utilize technology education in the form of software kvisoft flipbook maker which is integrated with local cultural arts and produced a development product in the form of learning media for mathematics flip book. The purpose of this study was to determine the process of developing flip book learning media and the effectiveness of learning media flip book in the learning process in class. The subjects in this study were 30 students consisting of 16 men and 14 women in rade VII junior high school in Indonesia. The development model in this study uses the 4D model which consists of the stages of define, design, develop, and disseminate. The development process in this study starts from the stage define by conducting initial initial analysis, student analysis, taskanalysis, concept analysis, and learning objective specifications; the next stage is the stage design by conducting a benchmark reference test, media selection, format, and initial media design; the next stage is the stage develop by conducting expert validation and development testing; and the last stage is the stage disseminate by packaging media and distributing media in the same school scope with different classes. The development of this learning media flip book can be an alternative choice in the use of mathematics learning media, especially in social arithmetic material.